2022
DOI: 10.15212/amm-2022-0005
|View full text |Cite
|
Sign up to set email alerts
|

Oral delivery of glutathione: antioxidant function, barriers and strategies

Abstract: Glutathione (GSH) is a tripeptide with potent antioxidant activity, which is involved in numerous basic biological processes and has been used for interventions in various degenerative diseases. However, oral delivery of GSH remains challenging, similarly to that of other protein and peptide drugs, because the physicochemical barriers in the gastrointestinal (GI) tract lead to low oral bioavailability. Although several approaches have been explored to improve delivery, such as co-administration with penetratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 131 publications
0
4
0
Order By: Relevance
“…Available evidence indicates that LRP1 serves a dual role as both an endocytic receptor and a signaling receptor [ 58 , 59 , 60 , 61 ]. With respect to the particles incorporating FITC-labeled bLf, the cellular uptake and transport appeared to be temperature- and energy-dependent, and the P app increased when the P-gp inhibitor (verapamil) was added, which prompted us to speculate that the cellular uptake of SLPs primarily occurs through endocytosis, with active transportation facilitated by P-glycoprotein (P-gp) also playing a significant role [ 62 , 63 , 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…Available evidence indicates that LRP1 serves a dual role as both an endocytic receptor and a signaling receptor [ 58 , 59 , 60 , 61 ]. With respect to the particles incorporating FITC-labeled bLf, the cellular uptake and transport appeared to be temperature- and energy-dependent, and the P app increased when the P-gp inhibitor (verapamil) was added, which prompted us to speculate that the cellular uptake of SLPs primarily occurs through endocytosis, with active transportation facilitated by P-glycoprotein (P-gp) also playing a significant role [ 62 , 63 , 64 ].…”
Section: Resultsmentioning
confidence: 99%
“…It not only elevated the expression of thiol groups on the cell surface but also promotes the increase of intracellular reducing substances such as glutathione (GSH). 45,46 Studies have shown that GSH, exported from the cytoplasm, could participate in cell surface disulfide covalent exchange reaction. 47 GSH content results showed that Res incubation significantly increased intracellular GSH content in both inflammatory and non-inflammatory macrophages (Fig.…”
Section: Res Promoted the Uptake Of La Npsmentioning
confidence: 99%
“…According to different sources, it can be divided into allografts of human origin and xenografts of animal origin ( FerreiraCastropaggiaro et al, 2011 ). This way provides a physical barrier from bacteria ( Wei et al, 2022 ) and trauma and can keep a moist microenvironment in the wound bed ( Dai et al, 2020 ), but allogenic skin grafts have the risk of immune rejection ( Iy and Al-Rubaiy, 2009 ).…”
Section: Representative Therapeutics For Wound Healingmentioning
confidence: 99%